Towards identification and cloning of the trypanotolerance genes in mouse - Iraqi, F.A.; Kemp, Stephen J.; Teale, A.J. (OAU/STRC, 2001)
The cartography in the high resolution of quantitative locus of character (QTL) is an important step towards the positional cloning or the positional identification of candidate genes. Recently, the use of descendants at the advanced inter-junction has been described for the dissection and the precise of (QTL) (Darvasi and Soller, 1995). In this study, we used the ATL to cartographe in detail the resistance to trypanosomiasis due to the infection by the Trypanosoma congolense with mice. First, we have cartographed three QTL TIR 1, 2 and 3 situated in the chromosomes 17, 5 and 1 respectively which enables to explain practically all the genetic variance in the population F2 produced by the junction of the resistant strain (C57BL/6 and of two susceptible strains A/J and BALB/C. The QTL have been cartographed regions measuring 20 to 40 cm. Next to the F2 cartography, we have developed 200 F6 mice at inter-junction C57BL/6XA/J. These 200 F6 mice became inoculated with T. congolense and 1750 of them which developed in infection became under the analysis. Sixty-six microsattelites situated at three QTL of 3 cm interval have been genotyped on mice representing extreme phenotypes, meaning the 200 mice which died first and the 200 which died last. The given genetics and phenotypic characters have been analysed with computer programes MAPMAKER/EXP/QTL and each of QTL has been cartographed at 5-10 cm. The preliminary results indicate that the QTL chromosome 17 TIR 1 consists at least two locus with LOD points of 13 and 15 separated by 0.5 cm. Similar results have been obtained with the QTL of chromosome 1, TR3, where indications have been found for two locus, each brought to a region separated by 5 cm with a 4 point LOD of 8 and 4 separated by 4 cm. The QTL of the chromosomes 5 TIR 2, have been cartographed at 5 cm with a point LOD of 3. Another mice are being genotyped in order to increase the resolution of the cartography, when the precise cartography of each QTL at a region of 0.5 cm is in the process of the strain blood relations at specific interval.